5G Green Mobile Communication Networks - Ge, Xiaohu; Zhang, Wuxiong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book focuses on the modeling, optimization, and applications of 5G green mobile communication networks, aimed at improving energy efficiency and spectrum utilization in 5G systems. It offers a balance between theoretical analysis and engineering practice, providing in-depth studies of a number of major topics, such as energy consumption models, optimization, system design, implementation, and performance evaluation. It also discusses four aspects of green communication in detail: cellular networks, resource management, wireless transmissions and multi-media communications. Further, this unique book comprehensively and systematically discusses green optimization in wireless mobile communications. As such it is a valuable resource for researchers, engineers, and graduate students in various fields, including telecommunications engineering, electrical and electronic engineering, and computer engineering, particularly those interested in green communications.
Challenges of 5G Green Communication Networks -- Energy Efficiency of 5G Wireless Communications -- Energy Efficiency of Cellular Networks -- Energy Efficiency of 5G Multimedia Communications -- Wireless Resource Management for Green Communication -- Energy Efficiency & Collaborative Optimization Theory of 5G Heterogeneous Wireless Multi networks.
Keywords: Telecommunication; Energy policy; Energy and state; Communications Engineering, Networks; Microwaves, RF Engineering and Optical Communications; Energy Policy, Economics and Management